Effect and comparative analysis of urease inhibitor AHA and low pH method on MICP reinforcement of calcareous sand - Hu, Jun; Zhan, Yahui; Yang, Yufei; Li, Zetian; Sun, Zhaokui; Yang, Yongchang; Zhang, Shuai (Frontiers in Microbiology, 2025)
In order to alleviate the problem of grouting blockage caused by the immediate action of bacteria and chemical reagents in the process of MICP reinforcement of sandy soil, this paper delays the generation rate of calcium carbonate by adding urease inhibitor AHA to the cementing solution and lowering the pH of the bacterial solution. The mechanism of action of the two methods was explored, and their effects were compared and analyzed. The results indicate that both AHA method and low pH method can effectively delay the generation rate of calcium carbonate and improve the reinforcement effect of MICP under different mechanisms of action. The reinforcement effect is best when the AHA content is 0.1% or when the pH drops to 5.5. Comparing the two methods, it was found that the solidification effect of low pH method on sandy soil was slightly higher than that of AHA method. This is because the calcium carbonate crystal size generated by low pH method is smaller than that of AHA method. Under similar calcium carbonate content, the smaller the crystal size, the more bonding points between calcium carbonate and soil, and the higher its strength. Exploring the mechanisms of action of the two methods, it was found that the AHA method delays the rate of urea hydrolysis catalyzed by urease. The low pH method acts on the binding process of carbonate ions and calcium ions after urea hydrolysis, as well as inhibiting urease activity. The two methods have different mechanisms of action, but both can achieve the goal of delaying the rate of calcium carbonate formation.